REVIEW OF UPPERMOST FURONGIAN TRILOBITES FROM SCANIA, SOUTHERN SWEDEN, BASED ON TYPE MATERIAL - Terfelt F. (My University, 2006)
The Scandinavian trilobites described in the classical papers by Moberg and Möller (1898) and Moberg (1898) are reviewed, based on the original type collections. The ten species and subspecies originally described are here considered to represent 12 species and subspecies, ranging in age from the latest Furongian (late Cambrian) through the Tremadocian (Early Ordovician). Lectotypes are selected for Parabolina (Parabolina) acanthura (Angelin), Acerocare ecorne Angelin and Westergaardia lata (Matthew). Leptoplastus claudicans (Moberg and Möller) is regarded as a junior subjective synonym of L. stenotus Angelin. These, and lectotypes formerly only figured by hand-drawings, are illustrated by high-resolution photographs.
Keywords: Furongian; Paleozoic::Cambrian::Furongian; Палеозой::Кембрийская::Фуронгский